ANALYSIS OF FACTORS INFLUENCING THE EVENT STUNTING WITH CHI-SQUARE METHOD APPROACH AUTOMATIC INTERACTION DETECTION IN NORTH SUMATRA - Arianti, Mei Yunina; Husein, Ismail; Widyasari, Rina (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
In statistics, one way to group (classify) a data mathematically is called classification. There are several types of classification methods, one of which is Chi-Square Automatic Interaction Detection, which is abbreviated as CHAID. CHAID method will be applied to North Sumatra stunting data. Stunting is a condition in which a person's height is shorter than that of other people of the same age. The dependent variable in the study was stunting, which was measured in infants aged 24-59 months, while the independent variable was a factor that affected stunting. The factors that influence the incidence of stunting in infants aged 24-59 months in North Sumatra based on the results of the analysis (CHAID) are family income, sanitation and water sources. From the results of the CHAID analysis, 5 different groups were obtained, namely: Infants aged 24-59 months who were stunted were infants with an economic income of IDR 1,000,000 - IDR 2,000,000 (98.4%) and inadequate sanitation (100%), Babies aged 24-59 months who are stunted are babies with an economic income of IDR 1,000,000 - IDR 2,000,000 (98.4%) and proper sanitation (93.2%), babies aged 24-59 months who are not stunted are infants with an economic income of Rp. 3,000,000 - Rp. 5,000,000 (95.5%). Infants aged 24-59 months who are not stunted are infants with an economic income of > Rp. 5,000,000 (99.5%) and adequate water sources (100%) and infants aged 24-59 months who are not stunted with an economic income of > IDR 5,000,000 (99.5%) and inadequate water sources (97.1%).